2020
DOI: 10.5114/fmpcr.2020.95313
|View full text |Cite
|
Sign up to set email alerts
|

Stress level and self-concept among type 2 diabetes mellitus patients in Indonesia

Abstract: Background. Diabetes mellitus has several complications related to mental health, such as stress and depression. Stress may disrupt the self-concept of a person with type 2 diabetes mellitus (t2Dm). Objectives. the aim of this study was to analyze the relationship between stress and self-concept among t2Dm patients in medan, indonesia. Material and methods. this is a cross-sectional study of a total of 100 subjects. the subjects were selected using convenience sampling. the primary data were collected from int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…25,26 Atherogenic index of plasma, on the other hand, is an instrument that has been used to assess the occurrence of atherosclerosis by using TG level as a marker. 27,28 Ultimately, small dense LDL-C leads to an increased risk for the development of CVD. [29][30][31] This study indicated that there was no relationship between the length of illness and age with ABI.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Atherogenic index of plasma, on the other hand, is an instrument that has been used to assess the occurrence of atherosclerosis by using TG level as a marker. 27,28 Ultimately, small dense LDL-C leads to an increased risk for the development of CVD. [29][30][31] This study indicated that there was no relationship between the length of illness and age with ABI.…”
Section: Discussionmentioning
confidence: 99%
“…Both aerobic and resistance exercises have a significant effect on the treatment of diabetes mellitus; they lower blood glucose, improve physical performance, and lower the depression scale [11,12]. However, despite the benefits of exercise [13], most people, particularly obese people, find it difficult to practice, so walking is a simple, easy, and inexpensive way to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Self-concept involves the perceptions, values, and self-confidence that affect a person’s behavior (Amelia et al, 2020) and it plays an important role in mental health (Ke et al, 2020). Individuals with a positive self-concept are better at developing and maintaining interpersonal relationships, resisting mental illness and physical diseases (Amelia et al, 2020) and accepting changes in life (Chew et al, 2016). A negative or poor self-concept is a risk factor for psychological health problems (Ke et al, 2020).…”
Section: Participants’ Experience Of the Self-concept Mode Of Adaptationmentioning
confidence: 99%